The branding of Kota Santri as a da’wah strategy by the Bireuen government in shaping the religious character of the community - Khaliluddin, Syeh; Arifin, Zainal; Rubino, Rubino (Islamic Communication Journal, 2025)
This study aims to analyze the “Kota Santri (Santri City)” branding strategy initiated by the Government of Bireuen Regency as a cultural da'wah approach to shaping the religious character of society. This research employs a qualitative method with a field study approach, involving in-depth interviews with policymakers, community leaders, and direct observation of socio-religious phenomena. The findings reveal that the “Kota Santri” branding is not merely a visual symbol but is internalized through government policies, the religious-oriented culture of civil servants, and increased religious activities within the community. Behavioral transformation is evident in the growing adherence to Islamic norms, the strengthening of religious identity in public life, and the emergence of a social culture aligned with Islamic values. This study offers novelty as initial research that positions religious branding as a form of Islamic communication strategy within the framework of local governance. The findings contribute to the development of contemporary da'wah concepts that integrate symbolic, policy-based, and social movement dimensions. ***** Penelitian ini bertujuan untuk menganalisis strategi branding “Kota Santri” yang diinisiasi oleh Pemerintah Kabupaten Bireuen sebagai pendekatan dakwah kultural dalam membentuk karakter religius masyarakat. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi lapangan, melalui wawancara mendalam dengan pemangku kebijakan, tokoh masyarakat, serta observasi fenomena sosial keagamaan di lapangan. Hasil penelitian menunjukkan bahwa branding “Kota Santri” tidak hanya menjadi simbol visual, tetapi juga terinternalisasi dalam kebijakan pemerintahan, budaya ASN, hingga aktivitas keagamaan di masyarakat. Transformasi perilaku masyarakat terlihat dari meningkatnya kepatuhan terhadap norma-norma islami, penguatan identitas religius dalam kehidupan publik, serta terbentuknya kultur sosial yang selaras dengan nilai-nilai keislaman. Penelitian ini memiliki kebaruan (novelty) karena menjadi studi awal yang memposisikan branding keagamaan sebagai strategi komunikasi Islam berbasis pemerintahan lokal. Temuan ini memberikan kontribusi terhadap pengembangan konsep dakwah kontemporer yang integratif antara simbol, kebijakan, dan gerakan sosial.